OAUNI optical observation of the supernova ASASSN-15lp - Pereyra, Antonio (2015)
During the commissioning runs of the National University of Engineering's Astronomical Observatory (OAUNI) project, we report optical imaging of the Type Ia SN ASASSN-15lp (ATel #7691, ATel #7692) on 2015-07-17.352 (UT). The measurement was gathered using the OAUNI 51cm telescope at the Huancayo Observatory, Peru (3300 masl at the central peruvian Andes). The observation was made under non-photometric clear skies and through an airmass of 1.4. A 180-second exposure in V filter yielded V = (15.86 +/- 0.05) mag. The zero point calibration was obtained using comparison stars in the neighborhood of the field. Our measurement is 28 days after the discovery (ATel #7691) and caution must be taken for contamination with the host galaxy. The OAUNI project is supported by UNI, The World Academy of Sciences (TWAS) and IGP.